Defending Moral Realism from Empirical Evidence of Disagreement. - Meyers, C. D. (Social Theory & Practice, 2013)
Recently, empirically minded philosophers have employed evidence of widespread, fundamental moral disagreement to argue against moral realism. I argue that the empirical evidence does not refute realism because the disagreement is consistent with certain pluralistic versions of moral realism that posit a set of pro tanto normative principles. Others have appealed to pluralism in defense of moral realism but have used pluralism to attack the empirically based approach to ethical theory. Although I argue that the empirical argument against moral realism fails, I defend the approach and suggest better ways that (pluralist) moral realism could be tested empirically.